The interplay between ferroptosis and inflammation: therapeutic implications for cerebral ischemia-reperfusion - He, Yuxuan; Wang, Jingyi; Ying, Chunmiao; Xu, Kang Li; Luo, Jingwen; Wang, Baiqiao; Gao, Jing; Yin, Zaitian; Zhang, Yunke (Frontiers in Immunology, 2024)
Stroke ranks as the second most significant contributor to mortality worldwide and is a major factor in disability. Ischemic strokes account for 71% of all stroke incidences globally. The foremost approach to treating ischemic stroke prioritizes quick reperfusion, involving methods such as intravenous thrombolysis and endovascular thrombectomy. These techniques can reduce disability but necessitate immediate intervention. After cerebral ischemia, inflammation rapidly arises in the vascular system, producing pro-inflammatory signals that activate immune cells, which in turn worsen neuronal injury. Following reperfusion, an overload of intracellular iron triggers the Fenton reaction, resulting in an excess of free radicals that cause lipid peroxidation and damage to cellular membranes, ultimately leading to ferroptosis. The relationship between inflammation and ferroptosis is increasingly recognized as vital in the process of cerebral ischemia-reperfusion (I/R). Inflammatory processes disturb iron balance and encourage lipid peroxidation (LPO) through neuroglial cells, while also reducing the activity of antioxidant systems, contributing to ferroptosis. Furthermore, the lipid peroxidation products generated during ferroptosis, along with damage-associated molecular patterns (DAMPs) released from ruptured cell membranes, can incite inflammation. Given the complex relationship between ferroptosis and inflammation, investigating their interaction in brain I/R is crucial for understanding disease development and creating innovative therapeutic options.Consequently, this article will provide a comprehensive introduction of the mechanisms linking ferroptosis and neuroinflammation, as well as evaluate potential treatment modalities, with the goal of presenting various insights for alleviating brain I/R injury and exploring new therapeutic avenues.